Development and evaluation of a potato slicer - DAYANA PAUL RAJESH MOHANAN SIMI POULOSE; Er. Prince M.V (Gudie) (Tavanur 2007 Kelappaji College of Agricultural Engineering and Technology)
Development and evaluation of a potato slicer
Development and evaluation of a potato slicer